Patient Self-Care Management: is Activity of Life Function Optimization Nursing Based Orem's Model Effective? - Alfonsius Kenjapluan; Fery Agusman; Muhammad Jamaluddin (Jurnal Ners, 2026)
This study is acknowledged because of the achievement of patient satisfaction that has not reached 100% of the 2024 range, and it is predicted that this is due to several patient safety incidents which are a form of poor service. The purpose of this research is expected to be the basis for a more holistic nursing innovation oriented towards the recovery of patients' life functions. The study used Quasi Experimental with a Pretest-Posttest Control Group design. The population is inpatients suffering from Typhoid Typhoid Fever. The sample technique used Purposive Sampling, and the sample calculation used the Lameshouw formula so that a sample of 44 patients was obtained which was divided into intervention groups and control groups. The results showed that there was a very significant difference between patient self-care before and after the Orem Model-based ALFON intervention. The application of ALFON based on the Orem Model was significantly more effective in improving the functional status of Typhoid Fever patients compared to nursing care methods. The most dominant factor influencing the success of the implementation of ALFON is the competence of nurses. ALFON based on the Orem Model is very effective in improving the independence and functional status of Typhoid Fever patients. Programs to improve nurse competencies and strengthen the work environment need to be priorities to support the successful implementation of this nursing model-based intervention.